2021
DOI: 10.11113/aej.v11.16874
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Shaking Table Test to Measure Liquefaction Potential of Prambanan Area, Yogyakarta, Indonesia

Abstract: This paper presents the experimental study of liquefaction potential for sandy soil in Prambanan Area, Yogyakarta, Indonesia, which underwent liquefaction due to the Mw 6.3 Jogja Earthquake on May 27, 2006. Shaking table tests considering the variation of acceleration and shaking duration were performed to investigate the liquefaction potential of sand. The liquefaction time stages including time to start liquefaction, time to start pore pressure dissipation, and liquefaction duration were observed. The percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The generation of r u resulted in a proportional increase in line with the seismic duration. Moreover, Deepsoil v7.0 reported a significant increase in pore water pressure in < 15 seconds, and the r u reached 0. a previous study generated a maximum r u at > 5 seconds (Mase et al, 2021). Another study conducted using numerical method showed that the time required to generate maximum r u was dependent on the seismic load and soil characteristics (Mase, 2017b;Prakoso et al, 2022).…”
Section: Resultsmentioning
confidence: 90%
“…The generation of r u resulted in a proportional increase in line with the seismic duration. Moreover, Deepsoil v7.0 reported a significant increase in pore water pressure in < 15 seconds, and the r u reached 0. a previous study generated a maximum r u at > 5 seconds (Mase et al, 2021). Another study conducted using numerical method showed that the time required to generate maximum r u was dependent on the seismic load and soil characteristics (Mase, 2017b;Prakoso et al, 2022).…”
Section: Resultsmentioning
confidence: 90%
“…The locally available sand that passes through a 425-micron and a retained 75-micron IS sieve was selected for the study, which fulfills the requirement recommended by Shields and Row [26]. Properties of all the drain materials used in the study are given in Table 2, and the particle size distribution is presented in Fig.…”
Section: Experimental Programmementioning
confidence: 99%
“…In areas with high seismicity, sand particles with no fulfill criteria for drainage resulted in liquefaction during earthquakes. Maze et al [26] showed from their study that the sand undergoes liquefaction under variation in dynamic loading. The criteria suggested by Shields and Row [27] could be used for selecting the size of sand used as drain material.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies were conducted to investigate liquefaction potential in parts of Yogyakarta [2], New Yogyakarta International Airport [3], and the Solo-Yogyakarta toll road. However, the study about potential liquefaction in the Yogyakarta-Bawen toll road project location is currently limited compared to other national strategic projects in Special Region of Yogyakarta.…”
Section: Figure 2 Liquefaction Susceptibility Zone Map In Central Jav...mentioning
confidence: 99%